Grounding Access to Justice Theory and Practice in the Experiences of Women Abused by Their Intimate Partners - Mosher, Janet E. (Windsor Yearbook of Access to Justice, 2015)
For women seeking to extricate themselves from the web of entrapment woven together by the multiple threads that make up the coercive control repertoire of their abusive intimate partners, it is often difficult to avoid engagement with legal systems. Yet, the legal systems they encounter—criminal, family, child welfare, immigration among them—are frequently unwelcoming (if not hostile), controlling, demeaning, fragmented and contradictory. While there has been a recent explosion of interest in “access to justice,” little attention has been paid to how we might conceptualize access to justice in a manner that speaks meaningfully to the circumstances of women who experience abuse in their intimate relationships. For such women, access to justice is curtailed not only by lack of representation, delays, costs, and procedural complexities—the obstacles commonly associated with access to justice failings—but by three inter-related phenomena: the enduring hold of an incident-based understanding of domestic violence; the failure of legal actors to curb men’s strategic use of legal systems to further their power; and the host of complications—contradictory expectations, inconsistent orders, repetitious proceedings, sweeping surveillance—that arise when women are compelled to navigate multiple intersecting legal systems. What is required, I argue, is a conceptualization of access to justice that places women’s safety and well-being at its core.